Extreme Thrombocytosis in Refractory ITP Post-Splenectomy With Associated Fatal Thromboembolism - Rithin Nedumannil; Emma Leitinger; Surender Juneja (SAGE Publishing, 2022)
Thrombopoietin (TPO)-receptor agonists have heralded a paradigm shift in the treatment of refractory immune thrombocytopenia (ITP). Reactive thrombocytosis has been described as a secondary effect of such therapies. However, the phenomenon of extreme thrombocytosis with morphology mimicking a myeloproliferative neoplasm (MPN) followed by fatal thromboembolism is unusual in this setting. Caution is required in the diagnosis of refractory ITP as well as TPO-receptor agonist dosing in such cases.